Pengaruh Penerapan E-Filling, Sosialisasi Perpajakan, Kinerja Account Representative, dan Sanksi Pajak terhadap Tingkat Kepatuhan WPOP - Kusumayanthi, Lyana Oka; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi, 2019)
This study aims to examine the effect of the application of e-filling, tax socialization, account representative performance and taxation penalty on individual taxpayer compliance at KPP Pratama Gianyar. This research was conducted at KPP Pratama Gianyar. The samples used were 100 respondents to the method of determining the sample was purposive sampling. The data collection techniques questionnaire. data analysis technique used is multiple linear regression analysis. Based on the results of the study showed that the application of e-filling, account representative performance and taxation penalty had a positive effect on WPOP compliance at KPP Pratama Gianyar, while tax socialization did not affect the WPOP at KPP Pratama Gianyar. Keywords : E-filing, tax socialization, account representative performance , taxation penalty, and individual taxpayer compliance .